A novel strategy for protein production using non-classical secretion pathway in Bacillus subtilis. Issue 1 (December 2016) - Chen, Jingqi; Zhao, Liuqun; Fu, Gang; Zhou, Wenjuan; Sun, Yuanxia; Zheng, Ping; Sun, Jibin; Zhang, Dawei
Abstract Background The Gram-positive bacteriumBacillus subtilis has been widely used as a cell factory for the production of proteins due to its generally regarded as safe (GRAS) nature and secretion capability. Of the known secretory pathways inB. subtilis, the majority of proteins are exported from the cytoplasm by Sec pathway, Tat pathway and ABC transporters, etc. However, the production of heterologous proteins byB. subtilis is unfortunately not that straight forward because of the bottlenecks in classical secretion pathways. The aim of this work is to explore a new method for protein production based on non-classical secretion pathway. Results Oned- psicose 3-epimerase (RDPE) which convertsd- fructose intod- psicose fromRuminococcus sp . 5_1_39BFAA was successfully and substantially secreted into the extracellular milieu without the direction of signal peptide. Subsequently, we demonstrated that RDPE contained no native signal peptide, and the secretion of RDPE was not dependent on Sec or Tat pathway or due to cell lysis, which indicated that RDPE is a non-classically secreted protein. Then, we attempted to evaluate the possibility of using RDPE as a signal to export eighteen reporter proteins into the culture medium. Five of eleven homologous proteins, two of five heterologous proteins from other bacterium and two heterologous proteins of eukaryotic source were successfully secreted into the extracellular milieu at different secretion levels when they were fused to RDPE mediated by a flexible 21-bp linker to keep a distance between two single proteins. Furthermore, the secretion rates of two fusion proteins (RDPE-DnaK and RDPE-RFP) reached more than 50 %. In addition, most of the fusion proteins retained enzyme or biological activity of their corresponding target proteins, and all of the fusions still had the activity of RDPE. Conclusions We found and identified a heterologous non-classically secreted protein RDPE, and showed that RDPE could direct proteins of various types into the culture medium, and thus non-classical protein secretion pathway can be used as a novel secretion pathway for recombinant proteins. This novel strategy for recombinant protein production is helpful to makeB. subtilis as a more ideal cell factory for protein production.